The WRKY transcription factor, WRKY13, activates PDR8 expression to positively regulate cadmium tolerance in Arabidopsis. (29th November 2018) - Sheng, Yibao; Yan, Xingxing; Huang, Ying; Han, Yangyang; Zhang, Cheng; Ren, Yongbing; Fan, Tingting; Xiao, Fangming; Liu, Yongsheng; Cao, Shuqing
Abstract: Cadmium (Cd) extrusion is an important mechanism conferring Cd tolerance by decreasing its accumulation in plants. Previous studies have identified an Arabidopsis ABC transporter, PDR8, as a Cd extrusion pump conferring Cd tolerance. However, the regulation of PDR8 in response to Cd stress is still largely unknown. In this study, we identified an Arabidopsis cadmium‐tolerant dominant mutant, designated xcd3‐D, from the XVE‐tagging T‐DNA insertion lines by a gain‐of‐function genetic screen. The corresponding gene was cloned and shown to encode a nuclear WRKY transcription factor WRKY13. Expression of WRKY13 was induced by Cd stress. Overexpression of WRKY13 resulted in decreased Cd accumulation and enhanced Cd tolerance, whereas loss‐of‐function of WRKY13 led to increased Cd accumulation and sensitivity. Further analysis showed that WRKY13 activates the transcription of PDR8 by directly binding to its promoter. Genetic analysis indicated that WRKY13 acts upstream of PDR8 to positively regulate Cd tolerance. Our results provide evidence that WRKY13 directly targets PDR8 to positively regulate Cd tolerance in Arabidopsis . Abstract : Cadmium (Cd) extrusion is an important mechanism conferring Cd tolerance by decreasing its accumulation in plants. Previous studies have identified an Arabidopsis ABC transporter, PDR8, as a Cd extrusion pump conferring Cd tolerance. However, the regulation of PDR8 in response to Cd stress is still largely unknown. In this study, we identified an Arabidopsis cadmium‐tolerant dominant mutant, designated xcd3‐D, from the XVEtagging T‐DNA insertion lines by a gain‐of‐function genetic screen. The corresponding gene was cloned and shown to encode a nuclear WRKY transcription factor WRKY13. Expression of WRKY13 was induced by Cd stress. Overexpression of WRKY13 resulted in decreased Cd accumulation and enhanced Cd tolerance, whereas loss‐of‐function of WRKY13 led to increased Cd accumulation and sensitivity. Further analysis showed that WRKY13 activates the transcription of PDR8 by directly binding to its promoter. Genetic analysis indicated that WRKY13 acts upstream of PDR8 to positively regulate Cd tolerance. Our results provide evidence that WRKY13 directly targets PDR8 to positively regulate Cd tolerance in Arabidopsis.